TRACE ELEMENT GEOCHEMISTRY AND SURFACE WATER CHEMISTRY OF THE BON AIR COAL, FRANKLIN COUNTY, CUMBERLAND PLATEAU, SOUTHEAST TENNESSEE - Shaver S.A.; McLamb E.D.; Kuers K.; Hower J.C.; Eble C.F. (My University, 2006)
Mean contents of trace elements and ash in channel, bench-column, and dump samples of the abandoned Bon Air coal (Lower Pennsylvanian) in Franklin County, Tennessee are similar to Appalachian COALQUAL mean values, but are slightly lower for As, Fe, Hg, Mn, Na, Th, and U, and slightly higher for ash, Be, Cd, Co, Cr, REEs, Sr, and V, at the 95% confidence level. Compared to channel samples, dump sample means are slightly lower in chalcophile elements (As, Cu, Fe, Ni, Pb, S, Sb, and V) and slightly higher in clay or heavy-mineral elements (Al, K, Mn, REEs, Th, Ti, U, and Y), but at the 95% confidence level, only As and Fe are different. Consistent abundances of clay or heavy-mineral elements in low-Br, high-S, high-ash benches that are relatively enriched in quartz and mire-to-levee species like Paralycopodites suggest trace elements are largely fluvial in origin. Factor analysis loadings and correlation coefficients between elements suggest that clays host most Al, Cr, K, Ti, and Th, significant Mn and V, and some Sc, U, Ba, and Ni. Heavy accessory minerals likely house most REEs and Y, lesser Sc, U, and Th, and minor Cr, Ni, and Ti. Pyrite appears to host As, some V and Ni, and perhaps some Cu, but Cu probably exists largely as chalcopyrite. Data suggest that organic debris houses most Be and some Ni and U, and that Pb and Sb occur as Pb-Sb sulfosalt(s) within organic matrix. Most Hg, and some Mn and Y, appear to be hosted by calcite, suggesting potential Hg remobilization from original pyrite, and Hg sorption by calcite, which may be important processes in abandoned coals. Most Co, Zn, Mo, and Cd, significant V and Ni, and some Mn probably occur in non-pyritic sulfides; Ba, Sr, and P are largely in crandallite-group phosphates. Selenium does not show organic or "clausthalite" affinities, but Se occurrence is otherwise unclear. Barium, Mn, Ni, Sc, U, and V, with strongly divided statistical affinities, likely occur subequally in multiple modes. For study area surface waters, highest levels of most trace elements occur in mine-adit or mine-dump drainage. Effluent flow rates strongly affect both acidity and trace element levels. Adit drainages where flow is only a trickle have the most acidic waters (pH 3.78-4.80) and highest trace element levels (up to two orders of magnitude higher than in non-mine site waters). Nonetheless, nearly all surface waters have low absolute concentrations of trace elements of environmental concern, and all waters sampled meet U.S. EPA primary drinking water standards and aquatic life criteria for all elements analyzed. Secondary drinking water standards are also met for all parameters except Al, pH, Fe, and Mn, but even in extreme cases (mine waters with pH as low as 3.78 and up to 1243 ppb Al, 6280 ppb Fe, and 721 ppb Mn, and non-mine dam-outflow waters with up to 18,400 ppb Fe and 1540 ppb Mn) downslope attenuation is apparently rapid, as down-drainage plateau-base streams show background levels for all these parameters. © 2005 Elsevier B.V. All rights reserved.
Keywords: BON AIR BITUMINOUS COAL; HYDROCHEMISTRY; MODE OF OCCURRENCE; SEWANEE, TENNESSEE; TRACE ELEMENTS; Pennsylvanian; Paleozoic::Carboniferous::Pennsylvanian; Палеозой::Каменноугольная